Sustainability, Human Well-Being, and the Future of Education - Cook, Justin W.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This open access book explores the key dimensions of a future education system designed to enable individuals, schools, and communities to achieve the twin twenty-first century challenges of sustainability and human well-being. For much of the twentieth century, Western education systems prepared students to enter the workforce, contribute to society and succeed in relatively predictable contexts. Today, people are at the controls of the planet$1 (Bmaking decisions that are dramatically reshaping social, economic, and environmental systems at a global scale. What is education$1 (Bs purpose in this new reality? What and how must we learn now? The volatility and uncertainty caused by digitalization, globalization, and climate change weave a common backdrop through each chapter. Using case studies drawn from Finland and the US, chapter authors explore various aspects of learning and education system design through the lenses of sustainability and human well-being to evaluate how our understanding and practice of education must transform. Using their scholarly research and experience as practitioners, the authors propose new approaches to preparing learners for a new frontier of the human experience fraught with risks but full of opportunity. .s
1. Learning at the Edge of History -- 2. Toward Robust Foundations for Sustainable Well-being Societies: Learning to Change by Changing How We Learn -- 3. Sustainable Wellbeing Society$1 (BA Challenge for a Public Sector Institution -- 4. Schools as Equitable Communities of Inquiry -- 5. Transforming Our Worldview Towards a Sustainable Future -- 6. Towards Solving the Impossible Problems -- 7. Unlocking the Future of Learning by Redesigning Educator Learning -- 8. Four-Dimensional Education for Sustainable Societies -- 9. Creativity, the Arts and the Future of Work -- 10. A New Narrative for the Future: Learning, Social Cohesion and Redefining (3z(BUs(3y (B-- 11. Climate Change Education: A New Approach for a World of Wicked Problems -- 12. CASE STUDY: Kaospilots$1 (BFrom Passive Listeners to Global Change Agents -- 13. CASE STUDY: Reggio Emilia and the Future of Early Childhood Education.s
Keywords: Environmental education; Educational policy; Education and state; Education$1 (BPhilosophy.s; Environmental and Sustainability Education; Educational Policy and Politics; Educational Philosophy